Transcriptome Responses of Wild Arachis to UV-C Exposure Reveal Genes Involved in General Plant Defense and Priming - Martins, Andressa Cunha Quintana; Mota, Ana Paula Zotta; Carvalho, Paula Andrea Sampaio Vasconcelos [UNESP]; Passos, Mario Alfredo Saraiva; Gimenes, Marcos Aparecido; Guimaraes, Patricia Messenberg; Brasileiro, Ana Cristina Miranda (MDPI, 2022)
Stress priming is an important strategy for enhancing plant defense capacity to deal with environmental challenges and involves reprogrammed transcriptional responses. Although ultraviolet (UV) light exposure is a widely adopted approach to elicit stress memory and tolerance in plants, the molecular mechanisms underlying UV-mediated plant priming tolerance are not fully understood. Here, we investigated the changes in the global transcriptome profile of wild Arachis stenosperma leaves in response to UV-C exposure. A total of 5751 differentially expressed genes (DEGs) were identified, with the majority associated with cell signaling, protein dynamics, hormonal and transcriptional regulation, and secondary metabolic pathways. The expression profiles of DEGs known as indicators of priming state, such as transcription factors, transcriptional regulators and protein kinases, were further characterized. A meta-analysis, followed by qRT-PCR validation, identified 18 metaDEGs as being commonly regulated in response to UV and other primary stresses. These genes are involved in secondary metabolism, basal immunity, cell wall structure and integrity, and may constitute important players in the general defense processes and establishment of a priming state in A. stenosperma. Our findings contribute to a better understanding of transcriptional dynamics involved in wild Arachis adaptation to stressful conditions of their natural habitats.
Keywords: Abiotic stress; Biotic stress; Cercosporidium personatum; Drought; Meloidogyne arenaria; Meta-analysis; Ultraviolet light